Non-leachable highly luminescent ordered mesoporous SiO2 spherical particles - Rocha, L. A. [UNESP]; Caiut, J. M. A. [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Martines, M. A. U.; Freiria, J. do C.; Dexpert-Ghys, J.; Verelst, M. (Iop Publishing Ltd, 2010)
Ordered mesoporous highly luminescent SiO2 particles have been synthesized by spray pyrolysis from solutions containing tetraethylorthosilicate (TEOS) and either cetyltrimethylammonium bromide (CTAB) or the block copolymer Pluronic F-68 as structure-directing agents. Rhodamine B (RhB)-containing samples were prepared by using a simple wet impregnation method followed by the growing of a second silica shell in order to prevent leaching of the dye. The obtained materials were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), powder x-ray diffraction (XRD), ultraviolet-visible spectroscopy (UV-vis) and photoluminescence (PL). Powders with polydisperse spherical grains were obtained displaying an ordered hexagonal array of mesochannels. Luminescence results reveal that RhB molecules have been successfully encapsulated into the channels of mesoporous particles as monomeric species and that a well-defined silica coating hindered dye leaching.